Extracochlear Stimulation of Electrically Evoked Auditory Brainstem Responses (eABRs) Remains the Preferred Pre-implant Auditory Nerve Function Test in an Assessor-blinded Comparison. Issue 1 (January 2019) - Causon, Andrew; O'Driscoll, Martin; Stapleton, Emma; Lloyd, Simon; Freeman, Simon; Munro, Kevin J.
Abstract : Objective: Electrically evoked auditory brainstem responses (eABRs) can be recorded before cochlear implant (CI) surgery to verify auditory nerve function, and is particularly helpful in to assess the function of the auditory nerve in cases of auditory nerve hypoplasia. This is the first study to compare three preimplant eABRs recording techniques: 1) standard extracochlear, 2) novel intracochlear, and 3) conventional intracochlear with the CI. Study Design: A within-participants design was used where eABRs were sequentially measured during CI surgery using three methods with stimulation from: 1) an extracochlear electrode placed at the round window niche, 2) two different electrodes on a recently developed Intracochlear Test Array (ITA), and 3) two different electrodes on a CI electrode array. Setting: New adults implantees (n = 16) were recruited through the Manchester Auditory Implant Centre and eABR measurements were made in theater at the time of CI surgery. Patients: All participants met the clinical criteria for cochlear implantation. Only participants with radiologically normal auditory nerves were recruited to the study. All participants were surgically listed for either a MED-EL Synchrony implant or a Cochlear Nucleus Profile implant, per standard practice in the implant centre. Outcome Measures: Primary outcome measures were: 1) charge (μC) required to elicit a threshold response, and 2) latencies (ms) in the threshold waveforms. Secondary outcome measures were: 1) morphologies of responses at suprathreshold stimulation levels and 2) wave V growth patterns. Results: eABRs were successfully measured from 15 participants. In terms of primary outcome measures, the charge required to elicit a response using the extracochlear electrode (median = 0.075 μC) was approximately six times larger than all other electrodes and the latency of wave V was approximately 0.5 ms longer when using the extracochlear electrode (mean = 5.1 ms). In terms of secondary outcomes, there were some minor quantitative differences in responses between extracochlear and intracochlear stimulation; in particular, ITA responses were highly variable in quality. The ITA responses were rated poor quality in 33% of recordings and in two instances did not allow for data collection. When not disrupted by open circuits, the median ITA response contained one more waveform than the median extracochlear response. Conclusions: In this first study comparing intracochlear and extracochlear stimulation, the results show that both can be used to produce an eABR that is representative of the one elicited by the CI. In the majority of cases, extracochlear stimulation was the preferred approach for preimplant auditory nerve function testing because of consistency, recordings that could be analyzed, and because extracochlear placement of the electrode does not require a cochleostomy to insert an electrode. Abstract : Supplemental Digital Content is available in the text